Advanced programming in the UNIX environment - Stevens, W. Richard. (Addison-Wesley professional computing series, 1993)
ANSI C. Files. Directories. File descriptors. System data files. Grpou files. Process control. Signals. Deamon processes. Interprocess communication. Data base library. Modem dialer. Pseudo terminals.